A New Framework for Quantifying Prehistoric Grave Wealth. Issue 1 (13th September 2022) - Nørtoft, Mikkel
Quantifying wealth in prehistoric graves is a long-standing unresolved issue. Previous approaches have focused on only one or a few aspects of grave wealth or grave good value, e.g. scarcity, or total number of object types (TOT), thus neglecting other value aspects, or, if combining value parameters, not in a reproducible or transparent way which makes application or comparison with other cases difficult. This study presents a new framework, QuantWealth, for combining different aspects of grave good value such as manufacturing time and skill, case-specific scarcity, prestige, and raw material distance, as well as estimated meat consumption from animal bones, all equally weighted and, in this study, used to perform PCA and calculate a Gini index. This Gini index can then be combined with Gini indices from more general grave wealth measures, including TOT and grave pit depth to form a more balanced Gini index of overall grave wealth. All of these parameters are calculated in a flexible and semi-automated framework based on experimental and prehistoric crafts reference data, which can be continuously updated and fine-tuned, flexibly integrates the respective chaînes opératoires, and which is openly available. As a case study, QuantWealth was applied to a dataset of 81 graves with preserved skeletal remains from 46 sites of the Corded Ware Culture (CWC) in Moravia, Czech Republic. PCA analysis of the grave good measures on these data along with age and sex/gender determination shows that males tend to be overall richer in grave goods than females, that juveniles have the highest meat expenditure, and that young adults rarely have visible meat expenditure.